Profile of gestational and congenital toxoplasmosis in a city in western Paraná (Research, Society and Development, 2022)
Toxoplasmosis is a parasitic disease that, when acquired during pregnancy can be transmitted to the fetus, being asymptomatic, causing sequelae to the newborn or leading to fetal death. Thus, this retrospective, quantitative and observational work analyzed data from pregnant women diagnosed with toxoplasmosis, in outpatient care during the years 2015 to 2019, in the city of Cascavel-PR. This study sought to analyze the efficiency of the drugs (Spiramycin, Pyrimethamine, Sulfadiazine and Folinic Acid), establish the result of the newborns' serology, in addition to obtain sociodemographic data of these pregnant women, analyzing age, marital status and education level. Fisher’s statistical test was used, with a significance level of α